2021
DOI: 10.1515/teme-2021-0036
|View full text |Cite
|
Sign up to set email alerts
|

Stitched open-loop measurements with a focal-distance-modulated confocal sensor

Abstract: The article presents measurements with a high-speed focal-distance modulated fibre-coupled confocal sensor integrated into a nano measuring machine (NMM-1). Combined with an appropriate signal processing, this axial beam modulating sensor yields a linear characteristic curve within a range of about 600 nm. This characteristic curve enables scans in closed-loop constant distance mode, where the controller of the NMM-1 keeps the distance between the measured surface and the sensor constant. Therefore, only one l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The setup consisted of a fibre-coupled confocal sensor firstly described in [67] and in its latest design, as it was applied for the investigations shown within this paper, in [68]. A thorough description of the sensor, including the theory of the signal formation based on general works on fibre-coupled confocal sensors of Gu et al [69], may be found in [70].…”
Section: Setupmentioning
confidence: 99%
“…The setup consisted of a fibre-coupled confocal sensor firstly described in [67] and in its latest design, as it was applied for the investigations shown within this paper, in [68]. A thorough description of the sensor, including the theory of the signal formation based on general works on fibre-coupled confocal sensors of Gu et al [69], may be found in [70].…”
Section: Setupmentioning
confidence: 99%
“…The single measurements are deliberately taken with overlapping areas to conduct the fine registration, which in optical surface metrology is known as sub-aperture stitching. 1 Most usual is the combination of an areal-topography measuring instrument, like a disc scanning confocal microscope or a coherence scanning interferometer, and a translational positioning system, [1][2][3][4][5][6] but also combinations with a rotatory positioning system, 7-9 a positioning system with more than three degrees of freedom [10][11][12][13][14] or a one-dimensional point distance sensor 15 have been shown. [16][17][18][19] Various algorithms are applied to conduct the fine registration or stitching with the correction of positioning errors in a variable number of degrees of freedom.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%